A study on risk and safety management for maintenance works at high rise building / Suhaliza Mhd Desa - Mhd Desa, Suhaliza (Faculty of Architecture, Planning and Surveying, 2013)
Building maintenance becomes a part of the building as it helps to operate performance of the building. How ever, the importance of the safety maintenance workers was neglected. The quality, safety and health practice are essential element in building maintenance to ensure that all occupants and workers always comfortable, safe and healthy. Regarding the OSHA Regulation, the implementation of the occupational safety, health and environment, and risk management for workplace and employee safety are compulsory. This research will discussed a few factors that should be considered by maintenance management to maintain a good level of quality, safety and health. The first step is identifies the risk and safety management implemented by the maintenance company to prevent the hazard. The purpose is to analyze the key or factor contributes to the hazard circumstance during maintenance works. Finally, the recommend was come out to give some sort of idea to the maintenances company to achieve high level of safety standard and reducing risk to prevent employees from having injury or loss of life, and avoid environmental and property damage. The result of the study was indicate that the maintenance company in case study building implement the Health, Safety and Environmental (HSE) policy accordance with the standard ISO14001 and OHSAS18001, and HIRARC preparation before a task was carried out to reduce risk. This is a part of the risk management for both of the company. From the study, it define that the accident happened are mostly cause by the employee’s lack of safety awareness.